Coinfection with Mycoplasma Pneumoniae and Chlamydia Pneumoniae in ruptured plaques associated with acute myocardial infarction - Higuchi,Maria de Lourdes (2003)
OBJECTIVE: To study atheromas, Mycoplasma pneumoniae (M. pneumoniae), and Chlamydia pneumoniae (C. pneumoniae). METHODS: C. pneumoniae was studied with immunohistochemistry and M. pneumoniae with in situ hybridization (ISH), in segments of coronary arteries (SCA) as follows: group A - thrombosed ruptured plaques (TRP) of 23 patients who died due to acute myocardial infarction (AMI); group B - 23 nonruptured plaques (NRP) of group A patients; group C - NRP of 11 coronary patients who did not die due to AMI; and group D - 11 SCA from patients with dilated cardiomyopathy or Chagas' disease without atherosclerosis. RESULTS: The mean number of C. pneumoniae+ cells/400x in groups A, B, C, and D was, respectively, 3.3±3.6; 1.0±1.3; 1.2±2.4; and 0.4±0.3; and the percentage of M. pneumoniae area was, respectively, 3.9±3.5; 1.5± 1.6; 0.9±0.9; and 0.4±0.2. More M. pneumoniae and C. pneumoniae were found in of group A than in group B (P<0.01). Good correlation was seen between the area of the vessel and the M. pneumoniae area in the plaque (r = 0.46; P=0.001) and between C. pneumoniae+ cells and CD4+ T lymphocytes (r = 0.42; P<0.01). The number of C. pneumoniae+ cells correlated with CD20+ B cells (r=0.48; P<0.01). CONCLUSION: M. pneumoniae and C. pneumoniae are more frequently found in TRP correlate with the intensity of the inflammation and diameter of the vessel (positive remodeling).